Feathers as bioresource: Microbial conversion into bioactive protein hydrolysates. (December 2018) - Callegaro, Kelly; Welter, Nicoly; Daroit, Daniel Joner
Graphical abstract: Highlights: Feather hydrolysates were produced by submerged cultivation with keratinolytic bacteria. Hydrolysates exhibited radical-scavenging, Fe 2+ -chelation and reducing power. Hydrolysates also exhibited antidiabetic and antihypertensive potentials in vitro . Hydrolysates produced by Bacillus sp. CL18 displayed the best enhanced bioactivities. Bioconversion of recalcitrant feathers is promising to obtain bioactive hydrolysates. Abstract: Feathers are recalcitrant protein-rich by-products generated by the poultry agro-industry, and valorization of residual biomasses from industrial processing is increasingly focused. Three feather-degrading Bacillus strains (CL18, CL33A, CL14) were used to convert feathers into feather hydrolysates (FH) during submerged cultivations, and the in vitro bioactivities of FHs were assessed. In feather broth (10 g/L feathers), Bacillus sp. CL18 degraded feathers more efficiently and the resulting FHs displayed enhanced antioxidant activities. With increasing feather concentrations, soluble protein was higher (9.02 mg/mL) after five days of cultivation with Bacillus sp. CL18 on feather broth containing 40 g/L feathers. This FH displayed antioxidant activities, as evaluated through the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azino-bis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS) radical-scavenging assays (34.7% and 80.3%, respectively), Fe 2+ -chelating ability (80.6%), and reducing power (0.518 Abs700 ). In vitro antihypertensive and antidiabetic activities of FH were demonstrated through inhibition of angiotensin I-converting enzyme (ACE; 89.7%) and dipeptidyl peptidase-IV (DPP IV; 95.7%) activities, respectively. Half-maximal effective/inhibitory concentrations of FH were 5.39, 15.12, 10.50, 1.61 and 1.52 mg/mL in the ABTS, DPPH, Fe 2+ -chelating, ACE- and DPP IV-inhibitory assays, respectively. Antioxidant, antidiabetic and antihypertensive potentials of FHs indicate microbial conversion as a suitable eco-friendly technology for feathers reclamation and valorization within the biorefinery concept.